Rare earth oxysulfide composite material and preparation method and application thereof

By using the core-shell structure nanosheet synthesis method of CuS shell and Eu doped Gd2O2S core at lower temperatures, the problem of rare earth sulfur oxide nanocrystal synthesis is solved, and the versatility of the material in biological applications is achieved.

CN119529839APending Publication Date: 2025-02-28XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411728367.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to synthesize high-quality monodispersed rare earth sulfur oxide nanocrystals at lower temperatures, and these materials do not perform well in functions such as photothermal conversion and nuclear magnetic imaging.

Method used

Core-shell structure nanosheets with CuS as the shell layer and Eu-doped Gd2O2S as the core were prepared at a lower temperature by a vulcanization-assisted synthesis method.

Benefits of technology

It realizes the versatility of rare earth sulfur oxide composites in biological applications, has excellent nuclear magnetic imaging performance and localization and calibration capabilities of cancer cells. At the same time, due to the photothermal properties of CuS, it can effectively inactivate cancer cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a rare earth oxysulfide composite material and a preparation method and application thereof.The rare earth oxysulfide composite material is a core-shell structure nanosheet with CuS as a shell and europium (Eu)-doped gadolinium oxysulfide (Gd2O2S) as a core, the rare earth oxysulfide composite material has optical imaging and nuclear magnetic resonance imaging functions, cancer cells can be positioned and calibrated, and due to the photo-thermal performance of CuS, the rare earth oxysulfide composite material can be applied to cancer cells. The cancer cells can be effectively inactivated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material synthesis, and particularly relates to a multifunctional rare earth oxysulfide composite material and a preparation method and application thereof. Background Art

[0002] In recent years, rare earth element compound nanocrystals, including oxides, fluorides, oxysulfides, etc., have attracted widespread attention due to their potential applications in electro-optical detectors, bioluminescent labels, drug carriers, etc. Among them, rare earth element oxysulfides with high chemical stability and high thermal stability are called wide-gap (4.6-4.8 eV) materials. As rare earth compound nanocrystals, they are efficient phosphors with wide excitation bands. However, the synthesis of high-quality monodisperse rare earth oxysulfide nanocrystals remains a huge challenge for researchers to date. According to the theory of hard and soft acids and bases, the hard Lewis acid RE 3+ With soft Lewis base S 2- There is a lack of affinity between them. Experiments have shown that there is a lack of effective sulfurization methods in the preparation of rare earth oxysulfide nanocrystals, because under generally mild conditions, it is difficult to introduce sulfur into rare earth oxides compared to synthetic sulfide semiconductors. It has been reported that high-temperature treatments of 600-1000 °C are required, such as calcination, two-step sol-gel pyrolysis, or sulfurization of rare earth hydroxide nanocrystals. However, these methods will cause the resulting nanocrystals to agglomerate, and it is difficult to control the size and dispersity of the particles during the synthesis process. Monodisperse nanoparticles can easily self-assemble into highly ordered patterns, which is convenient for manufacturing devices, so how to control the synthesis of monodisperse rare earth oxysulfide nanocrystals at relatively low temperatures has become a research hotspot and a problem that needs to be solved urgently.

[0003] Eu 3+ The luminescence properties of the 4f→5d transition are derived from its characteristic 4f→5d transition with different suitable excitation wavelengths. 3+ The excitation wavelengths in the doping system can be used to obtain multicolor emission. However, because their corresponding excitation spectra are discontinuous in the UV range, the color change trend in the above system is irregular. Rare earth sulfides (RE2O2S, RE = La, Gd, Y, Lu) have high chemical stability, low phonon energy (~520 cm -1 ), low symmetry and non-toxic, is one of the most effective fluorescent hosts. 3+ In the doped rare earth oxysulfides, there is O 2- →Eu 3+ and S 2- →Eu 3+ Charge transfer band, so Eu 3+The excitation spectrum of doped rare earth oxysulfides is continuous in the ultraviolet range, so this type of material has potential applications in various fields, such as color television picture tubes, field emission displays, biomedical fluorescence calibration and persistent phosphorescent devices.

[0004] However, Eu 3+ Doped rare earth sulfur oxides do not have good functions such as photothermal conversion and nuclear magnetic resonance imaging, and also lack certain catalytic activity. Their application in biomedicine needs to be studied.

[0005] Although the synthesis of multi-level nanostructures and composite materials can solve some of the shortcomings of single materials and realize the multifunctionality of nanomaterials, due to the mismatch between the crystal structure of rare earth oxysulfide and the crystal structure of semiconductors, the general methods for synthesizing multi-level nanostructures, such as solid-phase reaction method and combustion method, are not suitable for the synthesis of such materials. Therefore, the research on the synthesis of multi-level structure and multifunctional rare earth oxysulfide nanomaterials has attracted more and more attention. Summary of the invention

[0006] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a rare earth oxysulfide composite material and its preparation method and application. The rare earth oxysulfide composite material is a core-shell structure nanosheet with CuS as the shell and europium (Eu)-doped gadolinium oxysulfide (Gd2O2S) as the core. The nanosheet has optical imaging and nuclear magnetic resonance imaging functions, can locate and calibrate cancer cells, and due to the photothermal properties of CuS, can effectively inactivate cancer cells.

[0007] The present invention is achieved through the following technical solutions: A rare earth oxysulfide composite material is a nanosheet with a core-shell structure, wherein the outer shell of the nanosheet is CuS and the inner core is a Eu-doped Gd2O2S nanosheet.

[0008] Preferably, in the rare earth oxysulfide composite material, the molar ratio of Eu-doped Gd2O2S nanosheets to CuS is (1-2):1.

[0009] Preferably, in the rare earth oxysulfide composite material, the doping amount of Eu in the Gd2O2S nanosheets accounts for 1.6%-8% of the mass of the Gd2O2S nanosheets.

[0010] The method for preparing the rare earth oxysulfide composite material of the present invention comprises: S1, dispersing Eu-doped Gd2O2S nanosheets in cyclohexane to obtain a cyclohexane dispersion of Gd2O2S; dispersing sulfur powder in oleylamine to obtain an oleylamine dispersion of sulfur powder; dissolving copper acetylacetonate in chloroform to obtain a chloroform solution of copper acetylacetonate; S2, adding the oleylamine dispersion of sulfur powder to the cyclohexane dispersion of Gd2O2S, heating to a first reaction temperature for reaction, then adding a chloroform solution of copper acetylacetonate, heating to a second reaction temperature for reaction, and obtaining a reaction solution; S3, after the reaction is completed, ethanol is added to the reaction solution to precipitate, the precipitate is separated and dried to obtain a rare earth sulfur oxide composite material.

[0011] Preferably, in S1, the preparation method of the Eu-doped Gd2O2S nanosheets comprises: (1) dissolving gadolinium acetate and europium acetate in a mixed solvent of oleylamine and oleic acid to obtain a salt solution; heating, stirring and vacuumizing the salt solution, and then introducing an inert gas; (2) Under the protection of inert gas, the temperature of the salt solution is raised to 210-230°C, and the oleylamine dispersion of thioacetamide is added, and the temperature is continued to be raised to 270-300°C, and the reaction is carried out at this temperature; (3) After the reaction is completed and cooled to room temperature, anhydrous ethanol and cyclohexane are added to the obtained reaction solution, and the solid product is separated and dried to obtain a rare earth sulfur oxide composite material.

[0012] Preferably, in S2, the first reaction temperature is 70-90°C, and the reaction time at the first reaction temperature is 30-60 min; the second reaction temperature is 70-110°C, and the reaction time at the second reaction temperature is 1-3 h.

[0013] The present invention also provides a hydrophilic rare earth oxysulfide composite material, comprising the rare earth oxysulfide composite material as described above and a polyethyleneimine-polyethylene glycol polymer coated on the surface of the rare earth oxysulfide composite material.

[0014] Preferably, the mass ratio of the rare earth sulfur oxide composite material to the polyethyleneimine-polyethylene glycol polymer is 100:1.

[0015] The method for preparing the hydrophilic rare earth oxysulfide composite material of the present invention comprises: 1) dispersing the rare earth sulfur oxide composite material in cyclohexane to obtain a cyclohexane dispersion; dissolving (CH3)3OBF4 in N, N-dimethylformamide to obtain a (CH3)3OBF4 solution; 2) Mix the cyclohexane dispersion and the (CH3)3OBF4 solution, add toluene, and separate to obtain a solid product; 3) dispersing polyethyleneimine and polyethylene glycol in N, N-dimethylformamide, adding the solid product, stirring the mixture for reaction, and separating to obtain a hydrophilic rare earth oxysulfide composite material.

[0016] The present invention also provides the use of the rare earth oxysulfide composite material or the hydrophilic rare earth oxysulfide composite material in the preparation of nuclear magnetic resonance imaging contrast agents or drugs for treating cancer.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The multi-level structure Gd2O2S:Eu@CuS nanosheet provided by the present invention has a rare earth and semiconductor composite structure that combines the magnetic properties of the rare earth (Gd 3+ ), luminescence (Eu 3+ ) and the photothermal properties of semiconductors (CuS) are combined into one, making Gd2O2S: Eu@CuS composite nanosheets show excellent performance in biological applications. This composite nanomaterial can be used for nuclear magnetic resonance imaging and cell fluorescence labeling. At the same time, CuS in Gd2O2S: Eu@CuS composite nanosheets has semiconductor properties and is a p-type semiconductor material with high photothermal conversion efficiency. CuS is insoluble in water and most acids and has stable chemical properties. In biological cell applications, it can inactivate cancer cells through photothermal treatment. Therefore, Gd2O2S: Eu@CuS composite nanosheets have good application prospects in nuclear magnetic resonance imaging and cancer cell labeling and treatment.

[0018] Furthermore, Gd2O2S, CuS, Eu 3+ The relative dosage of Eu has a certain influence on the luminescence performance, photothermal performance and magnetic properties of the material, so the present invention limits its relative dosage. 3+ When the doping amount of CuS is too high, light quenching will occur and the material will no longer have the ability to emit red light; when the CuS coating amount is too high, the material will turn dark green, covering up the Eu 3+ The red light performance of Gd2O2S will be affected at the same time.

[0019] The present invention utilizes the fact that the edge of the two-dimensional ultra-thin nanostructure has more defects and active sites, and combines it with the sulfurization-assisted synthesis method to obtain a multifunctional Gd2O2S: Eu@CuS ultra-thin nanosheet composed of a rare earth luminescent / magnetic material and a semiconductor photothermal material. In the experimental process of preparing CuS-coated Gd2O2S: Eu nanosheets, the oleylamine dispersion of sulfur powder is first added to the cyclohexane dispersion of Gd2O2S, and heated to the first reaction temperature for reaction, in order to first coat a layer of S atoms on the surface of Gd2O2S: Eu, which is more conducive to the later Cu 2+Atoms combine with S atoms to generate CuS. If the reaction is directly carried out in one step, the generated CuS will separate from Gd2O2S: Eu and it is difficult to cover the outer layer of Gd2O2S: Eu to form a core-shell structure. By adjusting the experimental conditions such as reaction time, temperature, type of precursor and type of surfactant, nanosheets with uniform composition and a diameter of about 10-20 nm are obtained. This synthesis method is simple and convenient, the overall synthesis time is not long, and it usually has a high yield and good repeatability. High-quality Gd2O2S: Eu@CuS core-shell structure nanosheets can be obtained without the use of high-pressure reaction conditions. By extension, this synthesis method can also be used for the synthesis of various other similar nanomaterials, providing a novel idea for the more efficient, green, convenient and low-cost preparation of new multifunctional nanomaterials.

[0020] Furthermore, the present invention successfully prepared Eu 3+ Doped Gd2O2S: Eu ultrathin nanosheets with strong luminescence properties The present invention obtains a hydrophilic material Gd2O2S: Eu@CuS@PEG / PEI core-shell structure nanosheet by coating the outer layer with a polymer PEG / PEI (PEG / PEI is a commonly used polymer with hydrophilic properties, has no toxic side effects in the body, and has good biocompatibility), which can be used in biological experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 (a) Transmission electron microscopy (TEM) image and (b) low-magnification high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of Gd2O2S: Eu ultrathin nanosheets.

[0023] Figure 2 HAADF-STEM image of Gd2O2S:Eu ultrathin nanosheets and electron energy loss (EELS) elemental analysis images of elements Gd, Eu, O and S.

[0024] Figure 3 HAADF-STEM image of Gd2O2S: Eu@CuS composite ultrathin nanosheets and EELS elemental analysis images of Gd, Eu, O, S and Cu.

[0025] Figure 4 X-ray photoelectron spectroscopy (XPS) analysis of different elements in Gd2O2S: Eu@CuS composite ultrathin nanosheets: (a) Gd 4d, (b) Eu 3d, (c) O 1s, (d) S 2p and (e) Cu 2p.

[0026] Figure 5 XRD diffraction patterns of Gd2O2S: Eu@CuS composite ultrathin nanosheets and modified hydrophilic material Gd2O2S: Eu@CuS@PEG / PEI.

[0027] Figure 6 (a) Fluorescence spectra of Gd2O2S: Eu@CuS ultrathin nanosheets and modified hydrophilic material Gd2O2S: Eu@CuS@PEG / PEI (PL, λ ex = 365 nm) figure; (b) UV-Vis-NIR absorption spectra of Gd2O2S: Eu@CuS ultrathin nanosheets and the modified hydrophilic material Gd2O2S: Eu@CuS@PEG / PEI.

[0028] Figure 7 (a) The relationship between the Gd concentration and T2 relaxation rate of the hydrophilic Gd2O2S: Eu@CuS@PEG / PEI nanomaterials, with the inset showing the T2 magnetic resonance imaging (MRI) images of Gd2O2S: Eu@CuS@PEG / PEI at different Gd concentrations; (b) The temperature rise curves of aqueous solutions of Gd2O2S: Eu, Gd2O2S: Eu@CuS and Gd2O2S: Eu@CuS@PEG / PEI with the same concentration (1 mg / mL) under laser irradiation with a current power of 1 A and a wavelength of 980 nm.

[0029] Figure 8 This is the subcutaneous temperature rise curve of mice under laser irradiation with a power of 1A and a wavelength of 980 nm after the Gd2O2S: Eu@CuS@PEG / PEI ultrathin nanosheet aqueous solution of different concentrations obtained in Example 4 of the present invention was injected into the subcutaneous tissue of mice. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0031] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0032] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0033] The rare earth oxysulfide composite material Gd2O2S:Eu@CuS of the present invention is a core-shell structure nanosheet, the outer shell is CuS, and the inner core is Eu-doped Gd2O2S nanosheet.

[0034] The molar ratio of Eu-doped Gd2O2S nanosheets to CuS is (1-2): 1. The Eu-doping amount in the Gd2O2S nanosheets accounts for 1.6%-8% of the mass of the Gd2O2S nanosheets, preferably 4% (wherein the molar ratio is 5%, i.e., Gd2O2S: 5%Eu).

[0035] The present invention combines the sulfurization-assisted synthesis method to prepare Gd2O2S: Eu@CuS core-shell structure nanosheets based on Eu-doped Gd2O2S nanosheets, comprising the following steps: S1, dispersing Eu-doped Gd2O2S nanosheets in cyclohexane by ultrasonication to obtain a cyclohexane dispersion of Gd2O2S; dispersing sulfur powder in oleylamine to obtain an oleylamine dispersion of sulfur powder; dissolving copper acetylacetonate in chloroform to obtain a chloroform solution of copper acetylacetonate; S2, adding the oleylamine dispersion of sulfur powder to the cyclohexane dispersion of Eu-doped Gd2O2S, heating to a first reaction temperature for reaction, then adding a chloroform solution of copper acetylacetonate, heating to a second reaction temperature for reaction, and obtaining a reaction solution; S3, after the reaction is completed, ethanol is added to the reaction solution to precipitate, the precipitate is separated by centrifugation and dried to obtain a rare earth oxysulfide composite material Gd2O2S: Eu@CuS nanosheets.

[0036] The present invention prepares europium (Eu)-doped ultra-thin gadolinium oxysulfide (Gd2O2S) nanosheets by thermal decomposition and thermal injection. The specific preparation method includes: (1) dispersing thioacetamide in oleylamine by ultrasonication to obtain a thioacetamide-oleylamine dispersion; (2) adding gadolinium acetate (Gd(CH3COO)3) and europium acetate (Eu(CH3COO)3) into a mixed solvent of oleylamine and oleic acid to obtain a salt solution; (3) heating the salt solution in step (2) to 130°C, and stirring under vacuum at 130°C for 30 min to remove water and low-boiling-point solvents contained in the solvent. After the solution becomes clear and transparent, N2 gas is introduced to allow the subsequent reaction to proceed under N2 gas atmosphere; (4) When the temperature of the salt solution in step (3) is raised to 180-240°C, the oleylamine dispersion of thioacetamide in step (1) is injected therein, and the temperature is further raised to 240-300°C, and the reaction is carried out at this temperature for 1 hour; (5) After the reaction is completed, the mixture is cooled to room temperature, anhydrous ethanol and cyclohexane are added thereto, and the mixture is centrifuged to obtain Eu-doped Gd2O2S nanosheets; (6) The product obtained in step (5) is vacuum dried to obtain a Gd2O2S:Eu nanosheet powder sample.

[0037] The purpose of step (5) is to remove excess reaction solvent and surfactant in the product, wherein the non-polar solvent cyclohexane is used to remove excess non-polar surfactants such as oleylamine / oleic acid on the surface of the product, and the polar solvent anhydrous ethanol can cause the product coated with the non-polar surfactant to precipitate.

[0038] The present invention also prepares hydrophilic Gd2O2S: Eu@CuS@PEG / PEI core-shell structure nanosheets, and the preparation comprises the following steps: 1) Take Gd2O2S:Eu@CuS nanosheets and disperse them in cyclohexane by ultrasonication to obtain a cyclohexane dispersion; 2) Dissolve (CH3)3OBF4 in N, N-dimethylformamide (DMF) to obtain a (CH3)3OBF4 solution; 3) Mix the cyclohexane dispersion in step 1) and the (CH3)3OBF4 solution in step 2), stir at room temperature, add toluene, and centrifuge to collect the sample; 4) Disperse polyethyleneimine (PEI) and polyethylene glycol (PEG) in DMF by ultrasonication; 5) The sample obtained by centrifugation in step 3) is added to the solution in step 4), stirred at room temperature, and then centrifuged to obtain hydrophilic Gd2O2S: Eu@CuS@PEG / PEI core-shell structured nanosheets.

[0039] The rare earth oxysulfide composite material or the hydrophilic rare earth oxysulfide composite material of the present invention can be used for preparing nuclear magnetic resonance imaging (MRI) contrast agents or drugs for treating cancer.

[0040] The method for preparing the magnetic resonance imaging contrast agent of the present invention comprises the following steps: (1) Take agarose and prepare an agarose aqueous solution with a concentration of 5 mg / mL; (2) Prepare a sample aqueous solution with a certain concentration gradient, add a corresponding amount of agarose aqueous solution after ultrasonic dispersion, and disperse evenly by ultrasonic dispersion. No bubbles should be generated in the final solution, and it should be in a solid gel state after standing for MRI testing; (3) Use the same method to prepare gadoteric acid agarose solution as a standard reference for MRI measurement.

[0041] The Gd2O2S:Eu@CuS@PEG / PEI nanosheets of the present invention can be applied to cancer treatment in living animals, specifically: (1) Prepare aqueous solutions of Gd2O2S:Eu@CuS@PEG / PEI nanosheets with different concentrations.

[0042] (2) Aqueous solutions of Gd2O2S:Eu@CuS@PEG / PEI nanosheets with different concentrations were injected subcutaneously into mice, and the mouse epidermis was irradiated with a laser with a wavelength of 980 nm and a current power of 1 A.

[0043] (3) Use a visual infrared thermometer to record the temperature rise curve.

[0044] The present invention is further described in detail below in conjunction with examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. All raw materials and chemical reagents used are analytically pure.

[0045] Embodiment 1 This embodiment includes the following steps: (1) Weigh 450 mg (6 mmol) of thioacetamide and disperse it in 10 g of oleylamine by ultrasonication to obtain a yellow transparent solution, i.e., the thioacetamide-oleylamine dispersion; (2) Weigh 317.7 mg (0.95 mmol) of gadolinium acetate (Gd(CH3COO)3) and 16.5 mg (0.05 mmol) of europium acetate (Eu(CH3COO)3) and add them into a 50 mL three-necked flask; (3) Add 5 g of oleylamine and 2 g of oleic acid to the three-necked flask in step (2); (4) heating the solution in step (3) to 130°C, and stirring under vacuum at 130°C for 30 min to remove water and low-boiling-point solvents contained in the solvent. After the solution becomes clear and transparent, N2 gas is introduced to allow the subsequent reaction to proceed under N2 gas atmosphere; (5) When the reaction temperature of the reaction solution in the three-necked flask in step (4) is raised to 220°C, the oleylamine dispersion of thioacetamide in step (1) is injected therein, and the temperature is further raised to 280°C, and the reaction is carried out at this temperature for 1 h; (6) After the reaction is completed, the three-necked flask in step (5) is cooled to room temperature, 20 mL of anhydrous ethanol and 5 mL of cyclohexane are added thereto, and centrifuged (10000 rpm, 10 min) to obtain the product Eu-doped Gd2O2S nanosheets; (7) The product obtained in step (6) was placed in a vacuum drying oven at 65 °C and dried for 12 h to obtain a Gd2O2S: 5%Eu powder sample.

[0046] The morphology and elemental composition of the Gd2O2S: 5%Eu nanosheets obtained in this example were analyzed.

[0047] Figure 1 Figures a and b are transmission electron microscopy (TEM) and low-magnification high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images of Gd2O2S: 5%Eu, respectively. It can be seen from the figures that the morphology of Gd2O2S: 5%Eu is uniform and is an ultra-thin nanosheet structure with a diameter of 10-20 nm.

[0048] In order to prove that Eu 3+ In order to determine whether Eu was successfully doped into the Gd2O2S ultra-thin nanosheets, the element classification in the Gd2O2S: 5%Eu ultra-thin nanosheets was characterized in detail by HAADF-STEM and electron energy loss (EELS) spectra. Figure 2 The HAADF-STEM image in the figure proves that Gd2O2S: 5%Eu has good crystallinity. From the EELS elemental analysis image, it can be seen that the Gd, Eu, O and S that make up Gd2O2S: 5%Eu are evenly distributed, and there is no phase separation phenomenon, which indicates that Eu 3+ Successfully doped into Gd2O2S nanosheets.

[0049] Embodiment 2 This embodiment includes the following steps: (1) Weigh 450 mg (6 mmol) of thioacetamide and disperse it in 10 g of oleylamine by ultrasonication to obtain a yellow transparent solution, i.e., the thioacetamide-oleylamine dispersion; (2) Weigh 327.6 mg (0.98 mmol) of gadolinium acetate (Gd(CH3COO)3) and 6.6 mg (0.02 mmol) of europium acetate (Eu(CH3COO)3) and add them into a 50 mL three-necked flask; (3) Add 5 g of oleylamine and 2 g of oleic acid to the three-necked flask in step (2); (4) heating the solution in step (3) to 130°C, and stirring under vacuum at 130°C for 30 min to remove water and low-boiling-point solvents contained in the solvent. After the solution becomes clear and transparent, N2 gas is introduced to allow the subsequent reaction to proceed under N2 gas atmosphere; (5) When the reaction temperature of the reaction solution in the three-necked flask in step (4) is raised to 210°C, the oleylamine dispersion of thioacetamide in step (1) is injected therein, and the temperature is further raised to 270°C, and the reaction is carried out at this temperature for 1 h; (6) After the reaction is completed, the three-necked flask in step (5) is cooled to room temperature, 20 mL of anhydrous ethanol and 5 mL of cyclohexane are added thereto, and centrifuged (10000 rpm, 10 min) to obtain the product Eu-doped Gd2O2S nanosheets; (7) The product obtained in step (6) was placed in a vacuum drying oven at 65 °C and dried for 12 h to obtain a Gd2O2S: 2%Eu powder sample.

[0050] Embodiment 3 This embodiment includes the following steps: (1) Weigh 450 mg (6 mmol) of thioacetamide and disperse it in 10 g of oleylamine by ultrasonication to obtain a yellow transparent solution, i.e., the thioacetamide-oleylamine dispersion; (2) Weigh 300.9 mg (0.9 mmol) of gadolinium acetate (Gd(CH3COO)3) and 32.9 mg (0.1 mmol) of europium acetate (Eu(CH3COO)3) and add them into a 50 mL three-necked flask; (3) Add 5 g of oleylamine and 2 g of oleic acid to the three-necked flask in step (2); (4) heating the solution in step (3) to 130°C, and stirring under vacuum at 130°C for 30 min to remove water and low-boiling-point solvents contained in the solvent. After the solution becomes clear and transparent, N2 gas is introduced to allow the subsequent reaction to proceed under N2 gas atmosphere; (5) When the reaction temperature of the reaction solution in the three-necked flask in step (4) is raised to 230°C, the oleylamine dispersion of thioacetamide in step (1) is injected therein, and the temperature is further raised to 300°C, and the reaction is carried out at this temperature for 1 h; (6) After the reaction is completed, the three-necked flask in step (5) is cooled to room temperature, 20 mL of anhydrous ethanol and 5 mL of cyclohexane are added thereto, and centrifuged (10000 rpm, 10 min) to obtain the product Eu-doped Gd2O2S nanosheets; (7) The product obtained in step (6) was placed in a vacuum drying oven at 65 °C and dried for 12 h to obtain a Gd2O2S: 10%Eu powder sample.

[0051] Embodiment 4 This embodiment includes the following steps: (1) Weigh 50 mg of the Gd2O2S: 5%Eu nanosheets prepared in Example 1 into a round-bottom flask and ultrasonically disperse them in 10 mL of cyclohexane solution; (2) Weigh 3.2 mg of sulfur powder and disperse it in 3 mL of oleylamine. At the same time, weigh a certain amount of copper acetylacetonate and dissolve it in chloroform. (3) Add the oleylamine dispersion of sulfur powder to the cyclohexane solution containing the sample dispersed in step (1), stir at 70 °C for 30 min, add chloroform solution containing copper acetylacetonate after the reaction, and stir at 70 °C for 1 h; (4) After the reaction, 20 mL of ethanol was added to precipitate the sample, and the sample was centrifuged (10,000 rpm, 10 min) to obtain the product Gd2O2S: 5%Eu@CuS composite nanosheets, which were placed in a vacuum drying oven at 65 °C for 12 h to obtain a Gd2O2S: 5%Eu@CuS powder sample.

[0052] The element types and valence states of the Gd2O2S: 5%Eu@CuS composite nanosheets obtained in this example were analyzed.

[0053] In order to prove that the surface of Gd2O2S: 5%Eu nanosheets is coated with CuS, the electron energy loss (EELS) spectrum is used to classify and characterize the elements in the Gd2O2S: 5%Eu@CuS composite nanosheets. Figure 3 It can be seen from the EELS elemental analysis image that due to the coating of CuS, the signal of the O element in the Gd2O2S: 5%Eu structure is relatively weak, and the Cu element is distributed at the edge of the Gd2O2S: 5%Eu nanosheet. Gd, Eu, O and S are evenly distributed in the Gd2O2S: 5%Eu@CuS composite nanosheet.

[0054] X-ray photoelectron spectroscopy (XPS) was used to test and analyze the valence states of the elements Gd, Eu, O, S and Cu in the Gd2O2S: 5%Eu@CuS composite nanosheets. Figure 4 As shown in figure ae. Figure 4The two peaks at 140.8 eV and 145.8 eV in a represent the 4d of Gd in the Gd2O2S: 5%Eu@CuS structure. 5 / 2 and 4d 3 / 2 Orbital binding energy. Figure 4 As shown in the XPS data in b, the 3d electron orbit of the element Eu has two characteristic peaks, namely 3d 5 / 2 and 3D 3 / 2 , 1162.0 eV and 1135.1 eV peaks correspond to Eu 3+ 3D 5 / 2 and 3D 3 / 2 Orbital binding energy. Figure 4 The XPS double peak of O 1s in c indicates that there are two forms of oxygen in the Gd2O2S: 5%Eu@CuS composite nanosheets. The peak around 529.8 eV is generated by the lattice oxygen in Gd2O2S: 5%Eu, and the peak around 531.7 eV indicates the presence of adsorbed oxygen on the surface of Gd2O2S: 5%Eu@CuS composite nanosheets. Figure 4 d is the S 2p orbital energy spectrum, 161.3 eV and 162.9 eV are the S 2p 3 / 2 and 2p 1 / 2 Orbital binding energy, proving that it is S in Gd2O2S: 5%Eu@CuS 2- .exist Figure 4 931.2 eV and 952.3 eV in the e represent the 2p 3 / 2 and 2p 1 / 2 Orbital binding energy, which shows that Cu is divalent in Gd2O2S: 5%Eu@CuS.

[0055] Embodiment 5 This embodiment includes the following steps: (1) Weigh 37.8 mg of the Gd2O2S: 5%Eu nanosheets prepared in Example 1 into a round-bottom flask and ultrasonically disperse them in 10 mL of cyclohexane solution; (2) Weigh 3.2 mg of sulfur powder and disperse it in 3 mL of oleylamine. At the same time, weigh a certain amount of copper acetylacetonate and dissolve it in chloroform. (3) Add the oleylamine dispersion of sulfur powder to the cyclohexane solution containing the sample dispersed in step (1), stir at 70 °C for 30 min, add chloroform solution containing copper acetylacetonate after the reaction, and stir at 70 °C for 1 h; (4) After the reaction, 20 mL of ethanol was added to precipitate the sample, and the sample was centrifuged (10,000 rpm, 10 min) to obtain the product Gd2O2S: 5%Eu@CuS composite nanosheets, which were placed in a vacuum drying oven at 65 °C for 12 h to obtain a Gd2O2S: 5%Eu@CuS powder sample.

[0056] Embodiment 6 This embodiment includes the following steps: (1) Weigh 75.6 mg of the Gd2O2S: 5%Eu nanosheets prepared in Example 1 into a round-bottom flask and ultrasonically disperse them in 10 mL of cyclohexane solution; (2) Weigh 3.2 mg of sulfur powder and disperse it in 3 mL of oleylamine. At the same time, weigh a certain amount of copper acetylacetonate and dissolve it in chloroform. (3) Add the oleylamine dispersion of sulfur powder to the cyclohexane solution containing the sample dispersed in step (1), stir at 70 °C for 30 min, add chloroform solution containing copper acetylacetonate after the reaction, and stir at 70 °C for 1 h; (4) After the reaction, 20 mL of ethanol was added to precipitate the sample, and the sample was centrifuged (10,000 rpm, 10 min) to obtain the product Gd2O2S: 5%Eu@CuS composite nanosheets, which were placed in a vacuum drying oven at 65 °C for 12 h to obtain a Gd2O2S: 5%Eu@CuS powder sample.

[0057] Embodiment 7 This embodiment includes the following steps: (1) Weigh 100 mg of Gd2O2S: 5%Eu@CuS composite nanosheets and disperse them in 5 mL of cyclohexane by ultrasonication; (2) Weigh 50 mg of (CH3)3OBF4 and dissolve it in 5 mL of N, N-dimethylformamide (DMF); (3) After mixing the two solutions in steps (1) and (2), stir at room temperature for 10 min, add 10 mL of toluene, centrifuge at 10,000 rpm for 10 min, and collect the sample; (4) Weigh 100 mg of polyethyleneimine (PEI) and 100 mg of polyethylene glycol (PEG) and disperse them in 5 mL of DMF by ultrasonication. (5) The sample obtained by centrifugal separation in step (3) was added to the solution in step (4), and after stirring at room temperature for 24 h, the hydrophilic material Gd2O2S: 5%Eu@CuS@PEG / PEI core-shell structure nanosheets was obtained by centrifugal separation.

[0058] The crystal phase and structure of Gd2O2S: 5%Eu@CuS composite nanosheets and modified hydrophilic material Gd2O2S: 5%Eu@CuS@PEG / PEI were analyzed using X-ray powder diffraction analysis (XRD).

[0059] Use a mortar to grind the sample into powder and spread it on the sample table for XRD testing. Figure 5 As shown in the figure, since only a small amount of CuS is coated on the edge of Gd2O2S: 5%Eu, the diffraction peak of CuS is not found in the XRD diffraction pattern. At the same time, PEG / PEI is used in the experiment to modify the hydrophilicity of the outer layer of Gd2O2S: 5%Eu@CuS composite nanosheets. Since PEG / PEI is a polymer coating, the crystal XRD diffraction peak of Gd2O2S: 5%Eu@CuS@PEG / PEI is weakened after modification, but its phase state has not changed, and the XRD diffraction peak of hexagonal Gd2O2S is still the main body.

[0060] The optical properties of Gd2O2S: 5%Eu@CuS composite nanosheets were tested.

[0061] Gd2O2S: 5%Eu nanosheets coated with CuS did not affect Eu 3+ The luminescent properties, such as Figure 6 As shown in a, the blue curve is the fluorescence spectrum of Gd2O2S: 5%Eu@CuS composite nanosheets, that is, Eu 3+ Typical emission peak for red light: 581.9 nm, 5 D0→ 7 F0, 586.1 nm, 5 D0→ 7 F1 and 624.2 nm, 5 D0→ 7 In order to apply it in the field of biological cells, the hydrophilic material Gd2O2S: 5%Eu@CuS@PEG / PEI was obtained by modifying the outer layer of Gd2O2S: 5%Eu@CuS. Figure 6 It can be seen from the red curve in a that the outer layer of PEG / PEI weakens the luminescence intensity of the material. Figure 6 The inset in a is a luminescence photograph of the aqueous dispersion of Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheets under 365 nm ultraviolet light. It can be seen that Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheets can still emit visible red light under certain conditions, which can be used in biomarkers.

[0062] CuS is a new type of photothermal material that is low-cost and easy to prepare. It has strong absorption in the near-infrared region and can achieve high photothermal conversion efficiency of CuS materials. Figure 6 Figure b shows the UV-Vis-NIR spectrum of the material. The blue and red curves represent the UV-Vis-NIR spectra of Gd2O2S: 5%Eu@CuS and Gd2O2S: 5%Eu@CuS@PEG / PEI, respectively. It can be seen from the figure that Gd2O2S: 5%Eu@CuS has a strong absorption peak in the near-infrared region (700 nm-1900 nm). After coating with PEG / PEI, the absorption intensity of Gd2O2S: 5%Eu@CuS@PEG / PEI in the near-infrared region becomes relatively weak.

[0063] Nuclear magnetic resonance imaging and photothermal properties tests were carried out on Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheets.

[0064] In order to further study the magnetic properties of Gd and the photothermal properties of CuS in Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheets, firstly, different concentrations of Gd2O2S: 5%Eu@CuS@PEG / PEI were dispersed in agarose aqueous solution, and the hydrophilic material Gd2O2S: 5%Eu@CuS@PEG / PEI was subjected to magnetic resonance imaging test using a 0.5±0.05 T clinical MRI scanner. Figure 7 The inset in middle a shows the relationship between the magnetic resonance imaging enhancement ability of Gd2O2S: 5%Eu@CuS@PEG / PEI and the gadolinium concentration. As the gadolinium concentration increases, the T2-weighted image contrast gradually becomes brighter. Figure 7 The linear graph in a is the relationship between the concentration of gadolinium and the corresponding transverse relaxation of protons in its particle solution (1 / T2, red line), and K is calculated. T2 =16.24, proving that Gd2O2S: 5%Eu@CuS@PEG / PEI can be used as a potential contrast agent for magnetic resonance imaging applications.

[0065] On the other hand, the Gd2O2S: 5%Eu, Gd2O2S: 5%Eu@CuS and Gd2O2S: 5%Eu@CuS@PEG / PEI aqueous solutions with a concentration of 1 mg / mL were irradiated with a laser at a wavelength of 980 nm at a current power of 1 A. The infrared thermometer was used to measure the Figure 7The relationship curve between laser irradiation time and solution temperature rise shown in b. From the curve in the figure, it can be concluded that Gd2O2S: 5%Eu does not show photothermal effect, Gd2O2S: 5%Eu@CuS has a good photothermal effect, which can quickly increase the solution temperature to 52 ℃, while the heating rate and the maximum temperature of the hydrophilic material Gd2O2S: 5%Eu@CuS@PEG / PEI are weaker than those of Gd2O2S: 5%Eu@CuS, and the temperature rises to 35 ℃ in 5 min. =15 ℃. Generally speaking, when the material makes the temperature rise range of the solution =10 ℃, the material can be used for photothermal therapy of cancer cells, so Gd2O2S: 5%Eu@CuS@PEG / PEI has great application prospects in photothermal therapy of cancer cells.

[0066] Embodiment 8 The Gd2O2S: 5%Eu@CuS@PEG / PEI core-shell structure composite nanosheets prepared in Example 3 were applied to the subcutaneous photothermal performance test of mice. The specific steps are as follows: (1) Prepare 10 mg / mL and 200 mg / mL Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheet aqueous solutions, respectively.

[0067] (2) Aqueous solutions of Gd2O2S: 5%Eu@CuS@PEG / PEI nanosheets with different concentrations were injected subcutaneously into mice, and the mouse epidermis was irradiated with a laser with a wavelength of 980 nm and a current power of 1 A.

[0068] (3) Use a visual infrared thermometer to record the temperature rise curve.

[0069] Figure 8 This is the subcutaneous temperature rise curve of mice. It can be seen that the photothermal effect of Gd2O2S: 5%Eu@CuS@PEG / PEI composite nanosheets in living animals has certain application prospects and is expected to be used in the treatment of cancer in living animals.

Claims

1. A rare earth oxysulfide composite material, characterized in that: The rare earth oxysulfide composite material is a nanosheet with a core-shell structure, the shell of the nanosheet is CuS, and the core is a Eu-doped Gd2O2S nanosheet.

2. The rare earth oxysulfide composite material according to claim 1, characterized in that: The molar ratio of Eu-doped Gd2O2S nanosheets to CuS is (1-2):

1.

3. The rare earth oxysulfide composite material according to claim 1, characterized in that: The doping amount of Eu in Gd2O2S nanosheets accounts for 1.6%-8% of the mass of Gd2O2S nanosheets.

4. The method for preparing the rare earth oxysulfide composite material according to any one of claims 1 to 3, characterized in that: include: S1, dispersing Eu-doped Gd2O2S nanosheets in cyclohexane to obtain a cyclohexane dispersion of Gd2O2S; dispersing sulfur powder in oleylamine to obtain an oleylamine dispersion of sulfur powder; dissolving copper acetylacetonate in chloroform to obtain a chloroform solution of copper acetylacetonate; S2, adding the oleylamine dispersion of sulfur powder to the cyclohexane dispersion of Gd2O2S, heating to a first reaction temperature for reaction, then adding a chloroform solution of copper acetylacetonate, heating to a second reaction temperature for reaction, and obtaining a reaction solution; S3, after the reaction is completed, ethanol is added to the reaction solution to precipitate, the precipitate is separated and dried to obtain a rare earth sulfur oxide composite material.

5. The method for preparing the rare earth oxysulfide composite material according to claim 4, characterized in that: In S1, the preparation method of the Eu-doped Gd2O2S nanosheets comprises: (1) dissolving gadolinium acetate and europium acetate in a mixed solvent of oleylamine and oleic acid to obtain a salt solution; heating, stirring and vacuumizing the salt solution, and then introducing an inert gas; (2) Under the protection of inert gas, the temperature of the salt solution is raised to 210-230°C, and the oleylamine dispersion of thioacetamide is added, and the temperature is continued to be raised to 270-300°C, and the reaction is carried out at this temperature; (3) After the reaction is completed and cooled to room temperature, anhydrous ethanol and cyclohexane are added to the obtained reaction solution, and the solid product is separated and dried to obtain a rare earth sulfur oxide composite material.

6. The method for preparing the rare earth oxysulfide composite material according to claim 4, characterized in that: In S2, the first reaction temperature is 70-90°C, and the reaction time at the first reaction temperature is 30-60 min; the second reaction temperature is 70-110°C, and the reaction time at the second reaction temperature is 1-3 h.

7. A hydrophilic rare earth oxysulfide composite material, characterized in that: The invention comprises the rare earth oxysulfide composite material according to any one of claims 1 to 3 and a polyethyleneimine-polyethylene glycol polymer coated on the surface of the rare earth oxysulfide composite material.

8. The hydrophilic rare earth oxysulfide composite material according to claim 7, characterized in that: The mass ratio of the rare earth sulfur oxide composite material to the polyethyleneimine-polyethylene glycol polymer is 100:

1.

9. The method for preparing the hydrophilic rare earth oxysulfide composite material according to claim 7, characterized in that: include: 1) dispersing the rare earth sulfur oxide composite material in cyclohexane to obtain a cyclohexane dispersion; dissolving (CH3)3OBF4 in N, N-dimethylformamide to obtain a (CH3)3OBF4 solution; 2) Mix the cyclohexane dispersion and the (CH3)3OBF4 solution, add toluene, and separate to obtain a solid product; 3) dispersing polyethyleneimine and polyethylene glycol in N, N-dimethylformamide, adding the solid product, stirring the mixture for reaction, and separating to obtain a hydrophilic rare earth sulfur oxide composite material.

10. Use of the rare earth oxysulfide composite material according to any one of claims 1 to 3 or the hydrophilic rare earth oxysulfide composite material according to claim 7 or 8 in the preparation of a nuclear magnetic resonance imaging contrast agent or a drug for treating cancer.